ANALYTICAL METHOD DEVELOPMENT AND VALIDATION OF FLAVOXATE HCL WITH RP-HPLC - BHARDWAJ, AAKRITI; KUMAR, ROBIN; AIN, SHABNAM; KUMAR, BABITA; AIN, QURRATUL (International Journal of Pharmacy and Pharmaceutical Sciences, 2025)
Objective: To verify analytical methods, suitability for its intended use is the goal of validation by Reverse Phase-High Performance Liquid Chromatography (RP-HPLC) method. Methods: A validated method for determining flavoxate hydrochloride was created using HPLC, which is a sensitive, exact, and straightforward technique. The inertsilC18 (150 mm×4.6 mm, 5µm) is used in this approach. The buffer, which included 3g of 1-hexane sulphonic acid, 3 ml of Orthophosphoric Acid (OPA) and 3 ml of Triethylamine (TMA), was combined with Acetonitrile (ACN) in a 650:350 ratio to form the mobile phase. At 293 nm, Ultraviolet (UV) detection was done. Results: The Retaining time for flavoxate HCl was found to be 2.43 min. It was discovered that the linearity range of flavoxate HCl was 800-1200 µg/ml, and that the regression equation was y=17118x+80943. R 2 = 0.981 was found to be the linearity regression coefficient value. It was discovered that the RSD for intra-and inter-day precision was less than 2 %. Flavoxate HCl was discovered to have Limit of Detection (LOD)-83.13734 and Limit of Quantitation (LOQ)-251.9313 values of µg/ml and µg/ml, respectively. After statistical analysis, the results are deemed satisfactory. Conclusion: This technique can be used to analyze bulk forms of the antimuscarinic medication flavoxate HCl with success.